Development of VEGF-loaded PLGA matrices in association with mesenchymal stem cells for tissue engineering - Rosa, A. R. (2017)
The association of bioactive molecules, such as vascular endothelial growth factor (VEGF), with nanofibers facilitates their controlled release, which could contribute to cellular migration and differentiation in tissue regeneration. In this research, the influence of their incorporation on a polylactic-co-glycolic acid (PLGA) scaffold produced by electrospinning on cell adhesion and viability and cytotoxicity was carried out in three groups: 1) PLGA/BSA/VEGF; 2) PLGA/BSA, and 3) PLGA. Morphology, fiber diameter, contact angle, loading efficiency and controlled release of VEGF of the biomaterials, among others, were measured. The nanofibers showed smooth surfaces without beads and with interconnected pores. PLGA/BSA/VEGF showed the smallest water contact angle and VEGF released for up to 160 h. An improvement in cell adhesion was observed for the PLGA/BSA/VEGF scaffolds compared to the other groups and the scaffolds were non-toxic for the cells. Therefore, the scaffolds were shown to be a good strategy for sustained delivery of VEGF and may be a useful tool for tissue engineering.